New intensive techniques of orchard establishing with high budding seedlings - R. A. Oplachko; T. G. Prichko; I. L. Efimova (Новые технологии, 2018)
The results of the study of apple plantations productivity of various graft and rootstock combinations laid by a new planting material with high budding and dug in planting (an average of 15-20 cm) are presented. Influence of semi-dwarf SC 2U, MM 102 rootstocks and SK 7 dwarf rootstock on the timing of the introduction of an intensive type garden in the fruiting and productivity of plantations with different planting schemes: 4 x 0.9 m; 4 x 1.2 m; 4 x 2.4 m have been studied on the example of Prikubanskoe apple variety.